Online Shopping Frauds - Samal , Sarat K (International Journal of Psychosocial Rehabilitation, 2019)
CNP fraud or online shopping fraud is when a suspect enables fraudulent payment details or fraudulently acquired card cards to make online retail purchases without the consent of the account owner. Transaction scam is any type of fake or unlawful transaction by cybercriminal. The offender uses the Internet to deprive the victim of resources, personal property, interest or confidential information. Payment fraud is defined in three ways: loans that are illegal or not authorized. Missing merchandise, or robbed. The Ministry of Commerce and Industry has stated that online retail fraud has resulted in 13,873 cases since July 2016. The government has stated there is a database and a website for customers to send their concerns regarding online shopping scams. It is stated by the federal trade commission the steps that the consumer needs to follow when one opts for online shopping are getting details about the product one is buying, know about the cost of the product, beware of fake reviews etc. This paper reveals about online shopping frauds, how to identify fraudulent, how to report frauds.